Hydrothermal Synthesis of Free-Template Zeolite T from Kaolin - Arshad, Sazmal E.; Yusslee, Eddy F.; Lutfor, M. R.; Sarkar, Shaheen M.; Patuwan, Siti Z. (American Institute of Physics, 2017)
Free-template zeolite T crystals were synthesized via hydrothermal synthesis by utilizing the activated kaolin as silica and alumina source, with the molar composition of 1 SiO2: 0.04 Al2O3: 0.26 Na2O: 0.09 K2O: 14 H2O. Observation of the formation of free-template zeolite crystals were done at temperature 90°C, 100 °C and 110 °C respectively. It was therefore determined that during the 120 h of the synthesis at 90 °C, zeolite T nucleated and formed a first competitive phase with zeolite L. As temperature increases to 100 °C, zeolite T presented itself as a major phase in the system at time 168 h. Subsequently, development of Zeolite T with second competitive phase of zeolite W was observed at temperature 110 °C. In this study, XRD and SEM instruments were used to monitor the behavior of zeolite T crystals with respect of temperature and time. By using natural resource of kaolin clay as a starting material, this paper hence aims to provide new findings in synthesis of zeolite T using low energy consumption and low production cost.